Utilizing Geo-information for Mountain Community Adaptation - Khezri, Adish; Tuladhar, Arbind Man; Zevenbergen, Jaap (Journal on Geoinformatics, Nepal, 2017)
Mountain communities are vulnerable to diseases, malnutrition, and insecurity of land, which may lead to losing shelter and livelihood. This paper reveals that the current way of living of the mountain communities is unsustainable and vulnerable, and there is a lack in improving their adaptive ability for climate change adaptation. In order to understand how to improve the adaptive ability of the mountain community, this research makes a critical analysis of three case studies in Nepal, Indonesia and Peru. The results indicate the importance of geo-information as services or products at each scale ranging from global, regional, national, state/province, community to individual. The aim is to emphasize on access to geo-information that helps reduce the community vulnerability by providing a more effective adaptation program. Here we propose a framework for a Mountain Community Adaptive System (MCAS) which establishes the relationships between the vulnerability, livelihood and climate change adaptation.